The Interplay Among HIV, LINE-1, and the Interferon Signaling System - Zhao, Xu; Zhao, Yifei; Du, Juan; Gao, Pujun; Zhao, Ke (Frontiers in Immunology, 2021)
Human immunodeficiency viruses (HIVs) are retroviruses that replicate effectively in human CD4+ cells and cause the development of acquired immune deficiency syndrome (AIDS). On the other hand, type 1 long interspersed elements (LINE-1s or L1s) are the only active retroelements that can replicate autonomously in human cells. They, along with other active yet nonautonomous retroelements, have been associated with autoimmune diseases. There are many similarities between HIV and LINE-1. Being derived (or evolved) from ancient retroviruses, both HIV and LINE-1 replicate through a process termed reverse transcription, activate endogenous DNA and RNA sensors, trigger innate immune activation to promote interferon (IFN) expression, and are suppressed by protein products of interferon-stimulated genes (ISGs). However, these similarities make it difficult to decipher or even speculate the relationship between HIV and LINE-1, especially regarding the involvement of the IFN signaling system. In this review, we summarize previous findings on the relationships between HIV and innate immune activation as well as between LINE-1 and IFN upregulation. We also attempt to elucidate the interplay among HIV, LINE-1, and the IFN signaling system in hopes of guiding future research directions for viral suppression and immune regulation.